2017
DOI: 10.1002/ecs2.1710
|View full text |Cite
|
Sign up to set email alerts
|

Invisible but consequential: root endophytic fungi have variable effects on belowground plant–insect interactions

Abstract: Abstract. Endophytic fungi are ubiquitous in nature and can play important roles in regulating plantherbivore interactions. While some aboveground obligate symbionts are considered defensive mutualists of host plants, the importance of root endophytes in plant defense, especially against root-feeding insects, remains unclear. This study aimed to investigate the effects of root fungal endophytes on plant resistance against belowground herbivores and the recovery of host plants from damage. We grew the common gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…fungal endophytes and mycorrhizal fungi, can influence herbivory (30,55,73,99) and that the plant range of some insects is shaped by their microbiome (21). Although most research to date has focused almost exclusively on the fundamentals of microbial impacts on plant-insect interactions, there is a growing appreciation of opportunities for crop protection.…”
Section: Managing the Insect Microbiome For Improved Crop Resistance mentioning
confidence: 99%
“…fungal endophytes and mycorrhizal fungi, can influence herbivory (30,55,73,99) and that the plant range of some insects is shaped by their microbiome (21). Although most research to date has focused almost exclusively on the fundamentals of microbial impacts on plant-insect interactions, there is a growing appreciation of opportunities for crop protection.…”
Section: Managing the Insect Microbiome For Improved Crop Resistance mentioning
confidence: 99%
“…Nevertheless, a number of diverse endophytic fungi are known to also inhabit roots, forming variable associations with the plants, ranging from parasitic to mutualistic, without, however, causing apparent disease symptoms in plants ( Wilson, 1995 ; Schulz and Boyle, 2005 ; Hartley and Gange, 2009 ; Rodriguez et al, 2009 ). In contrast to AMF, the ecological roles of the most common endophytic fungi, especially those that are horizontally transmitted via spores (e.g., Ascomycetes), currently remain elusive although generally believed to also play an important role in plant protection against herbivores ( Jaber and Vidal, 2009 ; Rodriguez et al, 2009 ; Gan et al, 2017 ). Indeed, certain root endophytic fungi have been shown to increase the expression of defense-related genes and the production of secondary metabolites that may be relevant to plant defense ( Pieterse et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few studies involving endophytic fungi have reported negative effects on above ground herbivores thus enhancing their potent role in plant resistance to biotic stressors ( Jallow et al, 2004 ; Jaber and Vidal, 2009 , 2010 ; Muvea et al, 2014 ; Coppola et al, 2017 ; Contreras-Cornejo et al, 2018 ). Nevertheless, our understanding of endophytic fungi – plant – herbivore interactions is still at its infancy thus calling for more empirical studies on the significance of horizontally transmitted endophytes in plant–herbivore interactions ( Gan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is relatively unusual for a plant to be colonized by only one type of endophyte. The high number of species and high amount of microbial biomass in small populations suggest frequent multitrophic interactions between bacteria, micro-and macroscopic fungi, microfauna, plants and the environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%